The Engineering and Economic Feasibility Aplication of Bioconc on Concrete Quality Treatment in Low Heat Concrete - Makno Basoeki; Koespiadi Koespiadi (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
This paper discuss the concrete hydration thermal control with the economical and eco-friendly Method Statement, based on the basic perfomance of concrete bio-admixture, Bioconc, which is produce mico-filler, reduce the binder content up to 40%. The concrete hydration thermal sources is from the cement as binder, since Bioconc may reduce up to 40% binder content, the concrete hydration thermal can be controlled and worked as Low Heat Concrete. The paper limited discuss about the application of the Bioconc,for laboratory scale trial mix, Low Heat Concrete mock up modelling test and comparison with another 2 (two) Low Heat Concrete above mentioned [1] , [4] and does not discuss the Bioconc ingredient. The research started by laboratory scale trial mix Fc'25 Low Heat Concrete Bioconc based concrete Job Mix, from cement content reduction 20%, 25%, 30% and 40%. The attached result shows optimum jobmix is Fc'25 Low Heat Concrete Bioconc based concrete Job Mix on 40% cement as binder content reduction, was choosen as Low Heat Concrete Mix Mock Up. Later on, further research make mock up for sampling mass concrete dimension 1000x1000x2500 mm3 was executed. The attached Graph Thermal Monitoring Low Heat Concrete shows that the peak temperature occured 63,5 ?C in 29,5 hours after pouring and maximum thermal differential between LHC layers is 19,5 ?C. Another two Low Heat Concrete Method Statement, i.e.: Pre-cooling and Low Heat Concrete with Fly Ash 40%, Mock Up Graph Thermal Monitoring also attached for comparison study. The observation and analysis proof that, “Low Heat Concrete Hydration Thermal Reduction with Bioconc” is work simplifier and economically, for mass pouring. The most essential thing is that, the basic concept of Bioconc’s Low Heat Concrete on reducing the mass concrete cement-binder content means reducing CO2 emision in every concrete production, without any hazard impact to the environment. Its mean Bioconc based Low Heat Concrete contribute to develop the green technology and eco-friendly technology on the concrete industry as sustainable green technology.